Implementation of a Cloud-Based E-Learning System for Integrated Learning in Higher Education - Parini Parini; Sri Nur Rahmi; Fransiskus Ghunu Bili; Ahmya Ayaka (Yayasan Adra Karima Hubbi, 2024)
The integration of technology in higher education has gained significant momentum, with cloud-based e-learning systems emerging as a transformative approach to support integrated and flexible learning environments. Traditional learning systems often face limitations in scalability, accessibility, and resource-sharing, prompting the need for innovative solutions. Cloud-based e-learning systems offer a centralized platform that enhances collaboration, resource management, and learning continuity. This research explores the implementation of a cloud-based e-learning system in higher education institutions, focusing on its impact on learning outcomes and system efficiency. The study employs a mixed-method approach, combining quantitative surveys and qualitative interviews. Data were collected from 300 students and 50 faculty members across three universities that recently adopted cloud-based e-learning platforms. The research assessed system usability, learner engagement, and academic performance, alongside implementation challenges and benefits. The findings reveal that cloud-based e-learning systems significantly improve accessibility, resource-sharing, and collaboration among students and educators. Survey results indicated a 40% increase in learner engagement and a 35% improvement in resource utilization. Faculty interviews highlighted reduced administrative burdens and enhanced flexibility in course delivery. However, challenges such as data security concerns and the need for technical support were noted. The study concludes that cloud-based e-learning systems are a valuable tool for modernizing higher education. Addressing implementation challenges and ensuring continuous technical support are critical for maximizing their potential. Future research should explore long-term impacts and integration with emerging technologies to further enhance learning experiences.